2015
DOI: 10.14797/mdcj-11-3-189
|View full text |Cite
|
Sign up to set email alerts
|

A New Differential Diagnosis: Synthetic Cannabinoids-Associated Acute Renal Failure

Abstract: Synthetic cannabinoids (SCs) are herbal blends that use plant material with varying concentrations of synthetic analogues of cannabinoids. These products are sold as incense or potpourri and are labeled "Not for human use." Even so, rates of abuse are rapidly increasing worldwide, especially in the young adult population. An extensive network of users exists, and the products can easily be ordered on the Internet under various brand names, including the most popular ones, "K2" and "Spice." Not much is known ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 4 publications
1
15
0
Order By: Relevance
“…However, many of these cases were attributed to synthetic cannabinoid use based solely on statements by patients or witnesses, without analytical confirmation of the identity and amount of substances in bodily fluids or remaining drug products. Severe clinical complications that have been reported to be associated with synthetic cannabinoid use include convulsions and seizures (Adamowicz et al 2017;Bäckberg et al 2017;Bebarta et al 2012 Yirgin et al 2018), pneumonia and pulmonary infiltrates (Alhadi et al 2013;Alon and Saint-Fleur 2017;Berkowitz et al 2015;Chinnadurai et al 2016;Ö cal et al 2016), respiratory depression (Alon and Saint-Fleur 2017; Jinwala and Gupta 2012), supraventricular and ventricular arrhythmias (Davis and Boddington 2015;Ibrahim et al 2014;Ozturk et al 2019;Young et al 2012), myocardial ischemia and infarction (Clark et al 2015;Hamilton et al 2017;Hirapara and Aggarwal 2015;McIlroy et al 2016;McKeever et al 2015;Mehta et al 2017;Mills et al 2018;Mir et al 2011;Ozturk et al 2019;Shah et al 2016;Sherpa et al 2015;Tse et al 2014), takotsubo cardiomyopathy (Mohammed 2019), liver injury (Shahbaz et al 2018), acute kidney injury (Argamany et al 2016;Armstrong et al 2019;Bhanushali et al 2013;Buser et al 2014;El Zahran et al 2019;Gudsoorkar and Perez 2015;Kamel and Thajudeen 2015;Katz et al 2016b;…”
Section: Adverse Effects Of Synthetic Cannabinoidsmentioning
confidence: 99%
“…However, many of these cases were attributed to synthetic cannabinoid use based solely on statements by patients or witnesses, without analytical confirmation of the identity and amount of substances in bodily fluids or remaining drug products. Severe clinical complications that have been reported to be associated with synthetic cannabinoid use include convulsions and seizures (Adamowicz et al 2017;Bäckberg et al 2017;Bebarta et al 2012 Yirgin et al 2018), pneumonia and pulmonary infiltrates (Alhadi et al 2013;Alon and Saint-Fleur 2017;Berkowitz et al 2015;Chinnadurai et al 2016;Ö cal et al 2016), respiratory depression (Alon and Saint-Fleur 2017; Jinwala and Gupta 2012), supraventricular and ventricular arrhythmias (Davis and Boddington 2015;Ibrahim et al 2014;Ozturk et al 2019;Young et al 2012), myocardial ischemia and infarction (Clark et al 2015;Hamilton et al 2017;Hirapara and Aggarwal 2015;McIlroy et al 2016;McKeever et al 2015;Mehta et al 2017;Mills et al 2018;Mir et al 2011;Ozturk et al 2019;Shah et al 2016;Sherpa et al 2015;Tse et al 2014), takotsubo cardiomyopathy (Mohammed 2019), liver injury (Shahbaz et al 2018), acute kidney injury (Argamany et al 2016;Armstrong et al 2019;Bhanushali et al 2013;Buser et al 2014;El Zahran et al 2019;Gudsoorkar and Perez 2015;Kamel and Thajudeen 2015;Katz et al 2016b;…”
Section: Adverse Effects Of Synthetic Cannabinoidsmentioning
confidence: 99%
“…Studies indicate that heroin users, especially PWID, suffer from nephropathy (Cunningham, Brentjens, Zielezny, Andres, & Venuto, 1980;do Sameiro Faria, Sampaio, Faria, & Carvalho, 2003;May, Helderman, Eigenbrodt, & Silva, 1986). Other studies confirm that individuals using amphetamine (Ginsberg, Ertzman, & Schmidt-Nowara, 1970;Rifkin, 1977), cocaine (Merigian & Roberts, 1987;Norris et al, 2001;Sharff, 1984), alcohol (De Marchi, Cecchin, Basile, Bertotti, Nardini, & Bartoli, 1993;Perneger, Whelton, Puddey, & Klag, 1999), and potent cannabis (Abodunde, Nakda, Nweke, & Veera, 2012;Gudsoorkar & Perez Jr, 2015) are more likely to suffer from renal failure. It might be logically concluded that people with a history of drug consumption are more prone to contract renal insufficiency when they are infected to COVID-19; however, there is not any revealing evidence so far.…”
Section: Renal Insufficiencymentioning
confidence: 98%
“…3 The mechanism of renal injury is not yet clearly defined. 4 Acute tubular necrosis seems to be the leading etiology for AKI among these patients. However, classical hemodynamic collapse, hypotension or hypovolemic status for development of ATN may not be present.…”
Section: What Are Synthetic Cannabinoids?mentioning
confidence: 99%